(untitled) (Bangladesh Journal of Medical Education, 2017)
Accreditation of undergraduate medical education has been practicing worldwide in developed and developing countries. Fundamental ideas of this program is to ensure incorporation of ongoing global developments, evidence based scientific study and maintenance of minimum basic standard in education for population health and safety. WHO and WFME have been addressing for global standards in medical education and global accreditation of medical institutes for long time. Worldwide many countries have been responded to this call of global accreditation of medical colleges and medical education with their own context and experiencing benefits This exploratory cross sectional study has been conducted during the period of july-2014 to june-2015 to explore the opinion from key informants of medical education and views from young medical graduates. Data were collected from twenty one in-depth interviewee. Key informants stressed the necessity of an autonomous constitutional national independent accreditation body, faculty development and teacher evaluation, basic minimum resources in all listed medical colleges. Study recommended to accelerate the activities to establish national accreditation body for undergraduate medical education which will make way to achieve global accreditation in Bangladesh in coming future. Bangladesh Journal of Medical Education Vol.7(2) 2016: 9-16